2021
DOI: 10.3389/fmicb.2021.730355
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modifiers Revamp Secondary Metabolite Production in Endophytic Nigrospora sphaerica

Abstract: During plant interaction, endophytes provide benefits to the host plant. Endophytes also contribute a variety of structural attributes with biological potential. Nigrospora sphaerica, which produces phomalactone from Adiantum philippense L., was subjected to epigenetic modification. High-performance liquid chromatography (HPLC) and Gas chromatography-mass spectrometry (GCMS) analysis were used to determine secondary metabolite profiling. Epigenetic modifiers like DNA Methyltransferase (DNMT) and Histone deacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Sodium butyrate is an epigenetic modifier which inhibits the histone deacetylase activity, leading to the differentiation of the eukaryotic cells [ 86 , 87 ]. Previous studies showed that sodium butyrate treatment had the highest induction rate of 22 cryptic secondary metabolites from endophytic Nigrospora sphaerica [ 88 ]. The endophytic fungus isolate P03MB2 was then identified to share 100% homology with Penicillium chrysogenum based on the internal transcribed spacer (ITS) rRNA gene sequence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium butyrate is an epigenetic modifier which inhibits the histone deacetylase activity, leading to the differentiation of the eukaryotic cells [ 86 , 87 ]. Previous studies showed that sodium butyrate treatment had the highest induction rate of 22 cryptic secondary metabolites from endophytic Nigrospora sphaerica [ 88 ]. The endophytic fungus isolate P03MB2 was then identified to share 100% homology with Penicillium chrysogenum based on the internal transcribed spacer (ITS) rRNA gene sequence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…7. Ramesha et al (2021) studied six well-known modifiers for epigenetic modulation in the endophytic fungus Nigrospora sphaerica, including two DNMT inhibitors (5-azacytidine and hydralazine hydrochloride), a sirtuin activator (quercetin) and three HDAC inhibitors (SAHA, sodium butyrate and valproic acid). They came to conclusion that HDAC therapies produced more cryptic metabolites than DNMT treatments.…”
Section: Epigenetic Modulations In Fungal Endophytesmentioning
confidence: 99%
“…For instance, in the endophytic fungus Nigrospora sphaerica , epigenetic modifiers such as DNA methyltransferase and histone deacetylase inhibitors increased the expression of biosynthetic pathways. The accumulation of new metabolites was observed as a result of the activation of cryptic biosynthetic gene clusters in the microbes [ 50 ]. It is conceivable that the microbes synthesize metabolites that participate in drought stress responses.…”
Section: Introductionmentioning
confidence: 99%